Microfluidic DNA combing for parallel single-molecule analysis. (28th November 2018) - Wu, Shuyi; Jeffet, Jonathan; Grunwald, Assaf; Sharim, Hila; Gilat, Noa; Torchinsky, Dmitry; Zheng, Quanshui; Zirkin, Shahar; Xu, Luping; Ebenstein, Yuval
Abstract: DNA combing is a widely used method for stretching and immobilising DNA molecules on a surface. Fluorescent labelling of genomic information enables high-resolution optical analysis of DNA at the single-molecule level. Despite its simplicity, the application of DNA combing in diagnostic workflows is still limited, mainly due to difficulties in analysing multiple small-volume DNA samples in parallel. Here, we report a simple and versatile microfluidic DNA combing technology ( μ DC), which allows manipulating, stretching and imaging of multiple, microliter scale DNA samples by employing a manifold of parallel microfluidic channels. Using DNA molecules with repetitive units as molecular rulers, we demonstrate that the μ DC technology allows uniform stretching of DNA molecules. The stretching ratio remains consistent along individual molecules as well as between different molecules in the various channels, allowing simultaneous quantitative analysis of different samples loaded into parallel channels. Furthermore, we demonstrate the application of μ DC to characterise UVB-induced DNA damage levels in human embryonic kidney cells and the spatial correlation between DNA damage sites. Our results point out the potential application of μ DC for quantitative and comparative single-molecule studies of genomic features. The extremely simple design of μ DC makes it suitable for integration into other microfluidic platforms to facilitate high-throughput DNA analysis in biological research and medical point-of-care applications.